Disorders of Sex Development of Adrenal Origin - Finkielstain, Gabriela P.; Vieites, Ana; Bergadá, Ignacio; Rey, Rodolfo A. (Frontiers in Endocrinology, 2021)
Disorders of Sex Development (DSD) are anomalies occurring in the process of fetal sexual differentiation that result in a discordance between the chromosomal sex and the sex of the gonads and/or the internal and/or external genitalia. Congenital disorders affecting adrenal function may be associated with DSD in both 46,XX and 46,XY individuals, but the pathogenic mechanisms differ. While in 46,XX cases, the adrenal steroidogenic disorder is responsible for the genital anomalies, in 46,XY patients DSD results from the associated testicular dysfunction. Primary adrenal insufficiency, characterized by a reduction in cortisol secretion and overproduction of ACTH, is the rule. In addition, patients may exhibit aldosterone deficiency leading to salt-wasting crises that may be life-threatening. The trophic effect of ACTH provokes congenital adrenal hyperplasia (CAH). Adrenal steroidogenic defects leading to 46,XX DSD are 21-hydroxylase deficiency, by far the most prevalent, and 11β-hydroxylase deficiency. Lipoid Congenital Adrenal Hyperplasia due to StAR defects, and cytochrome P450scc and P450c17 deficiencies cause DSD in 46,XY newborns. Mutations in SF1 may also result in combined adrenal and testicular failure leading to DSD in 46,XY individuals. Finally, impaired activities of 3βHSD2 or POR may lead to DSD in both 46,XX and 46,XY individuals. The pathophysiology, clinical presentation and management of the above-mentioned disorders are critically reviewed, with a special focus on the latest biomarkers and therapeutic development.